Versatile functionalization of trifluoromethyl based deep blue thermally activated delayed fluorescence materials for organic light emitting diodes. (21st February 2018) - Liang, Xiao; Han, Hua-Bo; Yan, Zhi-Ping; Liu, Liang; Zheng, You-Xuan; Meng, Hong; Huang, Wei
Abstract : Four deep blue TADF compounds with trifluoromethyl-substituted phenyl/N-heterocyclic rings were investigated both as hosts and guests in OLEDs with excellent performance. Abstract : Thermally activated delayed fluorescence (TADF) materials have been thoroughly developed and have proven to be the most promising means to generate an efficient deep blue emission. In this work, we prepared a series of deep blue TADF emitters based on trifluoromethyl featuring phenyl and N-heterocyclic rings as electron-withdrawing units and carbazole as electron-donating moieties. Efficient organic light-emitting diodes (OLEDs) utilizing these emitters have a deep blue emission and a high external quantum efficiency of up to 20.4%. These blue emitters are among the bluest in the TADF based OLED category. They can also be implemented in OLED as hosts for green phosphorescent iridium(iii ) complexes, exhibiting high brightness and a decent external quantum yield.